Unsteady natural convection and statistical analysis in a CNT-water filled cavity with non-isothermal heating - Rahman, M. M.; Öztop, Hakan Fehmi; Steele, Michael; Naim, A. G.; Al-Salem, Khaled; Ibrahim, Talaat A. (Pergamon-Elsevier Science Ltd, 2015)
A computational study has been done in this work to investigate the effects of CNT-water nanofluids in a cavity with non-isothermal heating for higher Rayleigh numbers. The cavity is heated non-isothermally from the bottom wall, it is cooled from the top and vertical walls are adiabatic. Unsteady governing equations of heat and fluid flow are solved via finite element method for different parameters as Ra and phi. A correlation analysis shows that, when controlling for phi and tau there was a significant correlation between Ra and Nu(m). When controlling for Ra and phi there was a negative significant correlation between tau and Nu(m). It is also found that there is an optimum value for nanofluid volume fraction to control heat transfer, temperature distribution and flow field. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Carbon nanotube; Non-isothermal heating; Natural convection; Finite element; Correlation analysis